Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Which equation is equivalent to 6 (y+ 3) — 3 (у — 2) = 18?
A) 6у +3 — 3у – 2 = 18
B) 6у +3 + 3y – 2 = 18
C) 6y+ 18 — 3 — 6 = 18
D) 6y+ 18 — 3y + 6 = 18


Sagot :

Answer:

the answer is D

............

Answer:

The answer is (D)

Step-by-step explanation:

[tex]6(y + 3) - 3(y - 2) = 18 \\ 6y + 18 - 3y + 6 = 18 \\ [/tex]